INDYWIDUALNY STYL UCZENIA SIĘ A PREFEROWANE STRATEGIE – STUDIUM PRZYPADKU UCZNIA DYSLEKTYCZNEGO - Jaworska, Mariola (Neofilolog, 2018)
The aim of the article is to indicate the correlations between an individual learning style of a dyslectic child and their preferred strategies. The first part of the article discusses the developmental dyslexia which is considered to be the reflection of individual learning differences. The second part presents the portrait of a dyslectic student with particular emphasis put on their individual learning style and applied strategies. The final part of the text includes an attempt to indicate practical implications in the context of shaping autonomous attitudes of students with developmental dyslexia.